Behind the Times inside the new New York Times - Diamond, Edwin (Villard Books u.a., 1994)
Diamond examines the history of the Times, the Times' reviews of politics, and the politics of its reviews--book, theater, film, dance, music, and art.
Keywords: New York times; The New York Times; Geschichte 1970-1993; New York Times (dagblad); Hochschulschrift